2005
DOI: 10.1007/s00109-005-0020-6
|View full text |Cite
|
Sign up to set email alerts
|

SHP-1 promoter 2 methylation in normal epithelial tissues and demethylation in psoriasis

Abstract: SHP-1 promoter hypermethylation has been studied in hematopoietic cells and observed only in various types of lymphoma and leukemia. This study reports a contrasting situation in normal epithelial tissues and an association with skin pathogenesis, particularly in psoriasis. We investigated several cell lines, five of them were epithelial and six were hematopoietic, white blood cells from normal, healthy donors, and normal microdissected epithelium of kidney, liver, breast, cervix, lung, prostate, bladder, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(50 citation statements)
references
References 38 publications
1
49
0
Order By: Relevance
“…Treatment with HpaII confirmed demethylation in two of six SLE patients but in none of the HCs. The positive control was the DNA methylation of Daudi cell line cells (23). The negative control was the HpaII isoschizomer, MpsI, that cut the CpG sequences so that there were no PCR products.…”
Section: The Cd5-e1b Promoter Is Hypomethylated In Resting Sle B Cellsmentioning
confidence: 99%
“…Treatment with HpaII confirmed demethylation in two of six SLE patients but in none of the HCs. The positive control was the DNA methylation of Daudi cell line cells (23). The negative control was the HpaII isoschizomer, MpsI, that cut the CpG sequences so that there were no PCR products.…”
Section: The Cd5-e1b Promoter Is Hypomethylated In Resting Sle B Cellsmentioning
confidence: 99%
“…Similarly, hypomethylation of p16INK4A (antiapoptotic gene) has been reported in psoriasis, along with demethylation of one of the promoters of the SHP-1 gene, important for keratinocyte growth and proliferation (Ruchusatsawat et al 2006;Zhang et al 2007;Chen et al 2008). Importantly, the findings from these studies provides additional evidence that the molecular defects underlying polygenic skin diseases transcend single-gene mutations, and may be characterized by more global changes at the chromatin level associated with a multitude of downstream effects on gene expression.…”
Section: Aberrant Dna Methylation In Autoimmunerelated Skin Diseasesmentioning
confidence: 56%
“…Based on these genome-wide analyses, our studies have found that Tpaths and Tregs have different methylation density distribution in their autosomes and chromosome X. These novel results suggest epigenetic differences may contribute to the functional differentiation/specification of Tpaths vs. Tregs [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43].…”
Section: Both Foxp3mentioning
confidence: 94%
“…[37], and p16, SHP1, p15, and p21 in psoriasis [38][39][40]. The overexpression of two methyl CpG -binding domain (MBD) proteins, MBD2 and MBD4, may assoiated with the DNA hypomethylation in SLE CD4 + T cells [41].…”
Section: Journal Of Clinical Epigenetics Issn 2472-1158mentioning
confidence: 99%